Gen Z Digital Investment Intentions: An Analysis of Financial Literacy, Social Media, and Privacy Issues - Sri Endar Utami; Agni Astungkara; Triloka Mahesti; Arum Febriyanti Ciptaningtias (Journal of Social Commerce, 2025)
Economic uncertainty is inevitable for every individual, including Generation Z. One way to deal with this economic uncertainty is through financial planning, which also includes investment activities. This study aims to investigate the role of financial literacy, social media, and privacy concerns on investment intentions. This study involved 206 respondents who were Generation Z students in Semarang City, Indonesia. The results showed that financial literacy and the role of social media have a positive influence on Generation Z's intention to invest in digital platforms, while privacy concerns negatively affect their intention to invest in digital platforms. However, this study was unable to show a moderating relationship between privacy concerns and the role of social media and investment intentions in digital platforms.